Assessment of lead (Pb) residues in organs and muscles of slaughtered pigs at Nsukka and Environs in Enugu state, Nigeria - Felix, Obioha Chidiebere; John, Nwanta Anelom; Ekene, Ezenduka V (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Heavy metals are serious environmental pollutants and their uptake and accumulation in the ecosystem, beyond safe limits, would cause direct consequences to food chain and ultimately to man. The present study was undertaken to ascertain the presence and levels of lead (Pb) in muscles and organs of slaughtered pigs at Nsukka agricultural zone, Nigeria. Materials and methods: From a total of 160 slaughtered pigs, liver, kidney and muscle of each pig were collected and processed for the detection of lead residue using Atomic Absorption Spectrophotometer. Results: A prevalence rate of 81.25% was recorded for Pb residue in Nsukka agricultural zone. There is a strong association (P<0.0001) between occurrence of Pb residue and the source of samples. Mean concentrations of 0.0758 mg/kg, 0.1050 mg/kg and 0.0985 mg/kg were recorded in kidney, mean concentrations of 0.1676 mg/kg, 0.1235 mg/kg and 0.1955 mg/kg were recorded in liver and mean concentrations of 0.0598 mg/kg, 0.0870 mg/kg and 0.1020 mg/kg in muscle samples in Nsukka, orba and Obollo slaughter houses respectively. There is no significant (P<0.05) difference between the mean concentrations of the Pb in the liver, kidney and muscle samples (Nsukka, Orba and Obollo) and its maximum permissible levels (MPL). Conclusion: More than half of the samples were positive for Pb and few samples that exceeded the MPL may pose human health threat to pork consumers in the study area. http://doi.org/10.5455/javar.2016.c178